2005
DOI: 10.2106/jbjs.c.01637
|View full text |Cite
|
Sign up to set email alerts
|

Total Hip Replacement with the CLS Expansion Shell and a Structural Femoral Head Autograft for Patients with Congenital Hip Disease

Abstract: The CLS uncemented expansion shell, when used with a structural femoral head autograft, provides a reliable reconstruction, augments deficient acetabular bone stock, and allows placement of the socket at or close to the anatomic center of hip rotation in patients undergoing total hip arthroplasty to treat the sequelae of congenital hip disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Delimar et al [22] developed a new reconstruction method using a pedicle iliac graft after verifying that the deep circumflex artery was long enough to transfer this graft without resorting to micro-vascular anastomosis. Rozkydal et al [23] reported 43 cases of dysplastic hips treated with a CLS Expansion shell and a structural femoral head autograft. These options may be of interest when there is deficient acetabular bone stock in order to place the socket in its anatomical centre of hip rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Delimar et al [22] developed a new reconstruction method using a pedicle iliac graft after verifying that the deep circumflex artery was long enough to transfer this graft without resorting to micro-vascular anastomosis. Rozkydal et al [23] reported 43 cases of dysplastic hips treated with a CLS Expansion shell and a structural femoral head autograft. These options may be of interest when there is deficient acetabular bone stock in order to place the socket in its anatomical centre of hip rotation.…”
Section: Discussionmentioning
confidence: 99%
“…21 In some studies it had been assumed that Crowe types I and II correspond to Hartofilakidis type I, Crowe type III to Hartofilakidis type II and Crowe type IV to Hartofilakidis type III. 22,23 This assumption is not always valid because the anatomy of the acetabulum is variable and the amount of migration is not a definite criterion by which to judge the type of dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…In two previous reports, the 10-year survival of acetabular components other than the CLS expansion cup used in metal-on-metal bearings ranged from 94 to 96% with revision for any reason and 95 to 99% with revision for aseptic loosening as the end point [26,27]. The 10-year survival of the CLS expansion cup disregarding the bearing couple with revision for any reason ranged from 92.7 to 100% in three different studies [34][35][36]. This raises the question whether the CLS expansion cup performs inferiorly in Metasul-based metal-on-metal THR.…”
Section: Discussionmentioning
confidence: 98%